2009
DOI: 10.1104/pp.109.137885
|View full text |Cite
|
Sign up to set email alerts
|

Refining the Definition of Plant Mitochondrial Presequences through Analysis of Sorting Signals, N-Terminal Modifications, and Cleavage Motifs    

Abstract: Mitochondrial protein import is a complex multistep process from synthesis of proteins in the cytosol, recognition by receptors on the organelle surface, to translocation across one or both mitochondrial membranes and assembly after removal of the targeting signal, referred to as a presequence. In plants, import has to further discriminate between mitochondria and chloroplasts. In this study, we determined the precise cleavage sites in the presequences for Arabidopsis (Arabidopsis thaliana) and rice (Oryza sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
166
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 126 publications
(180 citation statements)
references
References 64 publications
11
166
2
1
Order By: Relevance
“…Analysis of experimentally determined mitochondrial presequences in plants (A. thaliana and O. sativa), based on the identification of the N terminus of the mature mitochondrial proteins, showed ∼10% of presequences had a length ≤23 aa (16). From the group of mitochondrial presequences ≤23 aa, we tested pL29 (19 aa) and pACD1 (20 aa) as substrates for OOP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of experimentally determined mitochondrial presequences in plants (A. thaliana and O. sativa), based on the identification of the N terminus of the mature mitochondrial proteins, showed ∼10% of presequences had a length ≤23 aa (16). From the group of mitochondrial presequences ≤23 aa, we tested pL29 (19 aa) and pACD1 (20 aa) as substrates for OOP.…”
Section: Discussionmentioning
confidence: 99%
“…In A. thaliana, mitochondrial presequences range from 19 to 109 aa (16); chloroplastic transit peptides usually are longer, ranging from 26 to 146 aa (9).…”
mentioning
confidence: 99%
“…The N-terminal presequences (PSs) range in size from 15-to 70-amino acid residues and have been demonstrated to be both necessary and sufficient for protein import into MT (von Heijne, 1986;Rapaport, 2003). Although no primary sequence consensus for targeting to the MT has been derived, detailed analyses have revealed several characteristic features, including the enrichment of hydroxylated and hydrophobic amino acids, an abundance of Arg residues, a lack of acidic amino acids, and a propensity to form an a-helix (Glaser et al, 1998;Huang et al, 2009). The configuration of positively charged and hydrophobic amino acids has been demonstrated to form an amphipathic a-helix in solution, and NMR analysis of the central mitochondrial outer membrane (MOM) import receptor, Tom20, in complex with an N-terminal PS revealed that the hydrophobic surface of the amphipathic a-helix binds to the hydrophobic groove of Tom20 (Abe et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…However, these sequences share preferences in physicochemical properties and the frequency of individual amino acids such as an overrepresentation of positively charged residues and, more specifically, of arginine, whereas negatively charged residues are nearly absent ( Figure 2B) (von Heijne et al, 1989;Huang et al, 2009). Accordingly, mitochondrial targeting signals can be generated quite easily de novo by mutations (Vassarotti et al, 1987) or insertion of arbitrary amino acid sequences at the N-terminus of a protein (Lemire et al, 1989).…”
Section: Mitochondrial Targeting Signalsmentioning
confidence: 99%
“…These unfolded proteins can interact with membrane-bound receptors on the surface of mitochondria, chloroplasts, or the ER and the transfer to the organellar membrane can be accelerated by cytosolic factors such as mitochondrial import stimulatory factor (MSF) (Hachiya et al, 1993) or 14-3-3 proteins for chloroplasts (May and Soll, 2000). Properties that distinguish mitochondrial and chloroplast preproteins have been elucidated (Huang et al, 2009), but the import mechanisms do not suggest a hierarchical relation between these targeting signals ( Figure 3B; [3]). In contrast, peroxisomal, nuclear, and cytosolic proteins are folded in the cytoplasm with the help of folding chaperones.…”
Section: Differences In the Import Mechanism Pose A Hierarchy Of Targmentioning
confidence: 99%